Neonatal Sepsis And Antibiotic Resistance: Emerging Challenges And Future Perspectives - kumarsharma, Sachin; Buddhadev, Mohit; Kirubakaran, J John; Patel, Hirni J; Harnawa, Anshul J; Nayak, S P Srinivas (Journal of Neonatal Surgery, 2025)
Neonatal sepsis remains a major cause of neonatal morbidity and mortality worldwide, particularly in low- and middle-income countries. The emergence of antibiotic-resistant bacterial strains has further complicated treatment options, leading to increased mortality and prolonged hospital stays. This review explores the epidemiology, risk factors, and common bacterial pathogens associated with neonatal sepsis. It also highlights the mechanisms of antibiotic resistance and current treatment strategies, including the limitations of broad-spectrum antibiotics. Additionally, we discuss the critical challenges in managing neonatal sepsis, such as the lack of neonatal-specific antibiotics and antibiotic stewardship gaps. Finally, future directions, including alternative therapies such as phage therapy, probiotics, and vaccines, are explored as potential solutions to combat neonatal sepsis and antibiotic resistance. Addressing these challenges requires a multidisciplinary approach to enhance infection control, improve antimicrobial stewardship, and develop novel therapeutic interventions to reduce the burden of neonatal sepsis.